2014
DOI: 10.1128/jvi.02484-14
|View full text |Cite|
|
Sign up to set email alerts
|

Determinants of Efficient Degradation of APOBEC3 Restriction Factors by HIV-1 Vif

Abstract: The APOBEC3 deoxycytidine deaminases can restrict the replication of HIV-1 in cell culture to differing degrees. The effects of APOBEC3 enzymes are largely suppressed by HIV-1 Vif that interacts with host proteins to form a Cullin5-Ring E3 ubiquitin ligase that induces 48 K-linked polyubiquitination (poly-Ub) and proteasomal degradation of APOBEC3 enzymes. Vif variants have differing abilities to induce degradation of APOBEC3 enzymes and the underlying biochemical mechanisms for these differences is not fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 78 publications
(174 reference statements)
3
38
1
Order By: Relevance
“…3B). Several previous observations describe that Vif binding to A3s is important but insufficient to induce degradation (44,75,76). Based on a recent wobble model (72), we speculate that the 50-110 region of FIV Vif contains the main Vif-A3 interaction interface, whereas the specific feline A3Z2 and A3Z3 interaction sites at the N-terminal 1-50 region provide additional stabilizing contacts.…”
Section: Discussionmentioning
confidence: 55%
“…3B). Several previous observations describe that Vif binding to A3s is important but insufficient to induce degradation (44,75,76). Based on a recent wobble model (72), we speculate that the 50-110 region of FIV Vif contains the main Vif-A3 interaction interface, whereas the specific feline A3Z2 and A3Z3 interaction sites at the N-terminal 1-50 region provide additional stabilizing contacts.…”
Section: Discussionmentioning
confidence: 55%
“…Coimmunoprecipitation (co-IP) assays were conducted as described previously (80). Briefly, the 293T cells (2.5 ϫ 10 6 cells per 75-cm 2 flask) were transfected with 1 g of total DNA.…”
Section: Methodsmentioning
confidence: 99%
“…These results indicate that binding detected by co-IPs is not a proper reporter for Vif-mediated counteraction affecting the protein levels. Indeed, several previous studies reported that binding of Vif and A3 is not the only determinant for complete Vif-medi- ated degradation (53,57,(83)(84)(85). Kitamura et al identified several residues between ␣2 and ␣3 helices of A3C binding to HIV-1 Vif (63).…”
Section: Discussionmentioning
confidence: 99%